Characterization the carotenoid productions and profiles of three Rhodosporidiumtoruloides mutants from Agrobacterium tumefaciens‐mediated transformation. Issue 8 (17th May 2017) - Lin, Xinping; Gao, Ning; Liu, Sasa; Zhang, Sufang; Song, Shuang; Ji, Chaofan; Dong, Xiuping; Su, Yichen; Zhao, Zongbao Kent; Zhu, Beiwei
Abstract: The red yeast Rhodosporidium toruloides is a known lipid producer capable of accumulating large amounts of triacylglycerols and carotenoids. However, it remains challenging to study its carotenoid production profiles owing to limited biochemical information and inefficient genetic tools. Here we used an Agrobacterium tumefaciens ‐mediated transformation (ATMT) to change its carotenoid production and profiles. We constructed R. toruloides NP11 mutant libraries with ATMT, selected three mutants with different colours, characterized their carotenoid products by high‐pressure liquid chromatography–mass spectrometry (HPLC‐MS) analysis and assured differences among those strains in terms of carotenoid production and its composition profiles. We then located T‐DNA insertion sites using the genome walking technology and provided discussions in terms of the new phenotypes. This study is the first of its kind to change the carotenoid production profiles in R. toruloides . Copyright © 2017 John Wiley & Sons, Ltd.